Functional characteristics of English professional linguistic markers in the practice of medico-legal support - A. A. Golubykh; O. N. Isaeva (Вестник Самарского университета: История, педагогика, филология)
The purpose of the study is to highlight and analyze functional characteristics of professional linguistic markers used in providing legal service protecting the rights of patients and doctors. The relevance of the paper is explained by the growing tendency to medical lawyers’ services on the one hand and an appeal to mass media discourse as an information media which forms conceptual and linguistic worldview on the other. The article examines language units which help to build professional discursive space in the field of medicine and law covering lawyers’ professional activity in the medical sphere and healthcare professionals in particular. The authors analyze current trends in legal assistance to doctors in their professional activities providing legal protection to injured patients. The scientific novelty of the article is that the language professional units within mass-media discourse by the material of The Patients Association and Doctors Defence Service in the framework of Medical Law concept permitting to study linguistic markers, their interaction and functional potential are described. The empirical study includes such methods as observation, description and classification, functional and pragmatic analysis, discourse analysis, linguistic and semantic analysis. As a result of the study, language units reflecting problem areas and modern vectors in medico-legal sphere of Great Britain are systematized and analyzed. The authors’ observations showed that the professional linguistic markers under analysis represent emerging trends in British medical law characterized by the establishment and maintenance of the patient's right to quality medical care; popularization of private medical services by general practitioners and the National Health Service; and increasing popularity of professional liability insurance for private dentists, etc. The conclusion about language functions – informative, communicative, general-cognitive and pragmatic – realized by verbal units is made.